2012
DOI: 10.1080/09540121.2012.672721
|View full text |Cite
|
Sign up to set email alerts
|

Barebacking and sexual health in the French setting: “NoKondom Zone” workshops

Abstract: Barebacking has been, since its emergence in the 1990s, a very controversial issue, and has as many definitions as authors writing about it. In France, sexual risk reduction strategies have been very contentious, and the advent of the bareback phenomenon increased this conflictual situation. This state of affairs has prevented the identification of needs and development of adequate programs for people not using condoms. In December 2008, a peer sexual health workshop, organized on a monthly basis and taking pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…There is an example in France of monthly workshops for gay men who were into barebacking conducted over a year (a deliberate and conscious choice to engage in risky sexual behaviour knowing that there are risks involved) (Suarez and Miller, 2001). They showed that after attending the workshops, they felt less isolated or discriminated against and improved their psychosocial well-being (Rojas Castro et al, 2012). The French study was hosted by an LGBT organisation but was facilitated by the members of the group who identified with the practice of barebacking.…”
Section: Sexual Health and Hivmentioning
confidence: 99%
“…There is an example in France of monthly workshops for gay men who were into barebacking conducted over a year (a deliberate and conscious choice to engage in risky sexual behaviour knowing that there are risks involved) (Suarez and Miller, 2001). They showed that after attending the workshops, they felt less isolated or discriminated against and improved their psychosocial well-being (Rojas Castro et al, 2012). The French study was hosted by an LGBT organisation but was facilitated by the members of the group who identified with the practice of barebacking.…”
Section: Sexual Health and Hivmentioning
confidence: 99%
“…There is an example in France of monthly workshops for gay men who were into barebacking conducted over a year (a deliberate and conscious choice to engage in risky sexual behaviour knowing that there are risks involved) (Suarez and Miller, 2001). They showed that after attending the workshops, they felt less isolated or discriminated against and improved their psychosocial well-being (Rojas Castro et al, 2012). The French study was hosted by an LGBT organisation but was facilitated by the members of the group who identified with the practice of barebacking.…”
Section: Sexual Health and Hivmentioning
confidence: 99%